Movements and diving of ringed seals (Phoca hispida) in Svalbard - Kovacs, Kit M.; Gjertz, Ian; Wiig, Øystein; Lydersen, Christian (Norwegian Polar Institute, 2008)
Seven post-moulting ringed seals (Phoca hispida) were equipped with Satellite Linked Dive Recorders in Svalbard in July 1996 to determine if ringed seals conduct long-distance post-moulting feeding excursions, and to obtain details of their diving behaviour. The transmitters were programmed to transmit every other day, and had a depth range of 0-470 m and a resolution of 2 m. The minimum depth to be considered a dive was set to 2 m. Dive depth and duration were recorded into 14 intervals. The mean duration of tags was 206 days (range 103-325). Two seals swam 400 km north to the drifting pack ice (82°N). The rest undertook more local movements. Forty-eight percent of all dives were shallower than 20 m and 90% were shallower than 100m. Ninety-five percent of all dive durations were shorter than 10 min, and 99.5% were shorter than 15 min. This study has shown that adult ringed seals undertake varying patterns of post-moulting excursions.